Novel Application of Solubilizing Properties of Solids (Mixed Solvency Concept) for Extraction of Active Constituents from Herbal Drug Powder and Formulation and Evaluation of Topical Oily Solution of Curcumin Extract - Soni, Simran (Asian Journal of Pharmaceutics (AJP), 2022)
Background: Since the beginning of time, humankind has employed herbal and medicinal plants as a source of food and medicine. Plant bioactive chemicals are currently of great research interest. However, extracting them as part of phytochemical and/or biological studies brings unique problems. Many techniques for the extraction of bioactive components have been devised by herbalists or scientists to indemnify the effectiveness and efficacy of the raw medications used to treat illness. The mode of extraction of active phytochemicals is receiving a lot of attention to reduce the costs associated with synthesis and separation. As a result, the extraction of active compounds from plants requires a proper procedure for extraction and techniques that provide extracts and fractions high in bioactive components, and also the solvents used in extraction do not harm humans as well as nature. As a result, they have a significant impact on yield, the nature of phytochemical content, and so on. Objectives: The purpose of this paper is to discuss and describe that solvents for extraction which shall be ecofriendly, safe, and also can be recovered easily by evaporation and preparation of the formulation using blends derived by idea of mixed solvency concept. Materials and Methods: Before extraction and formulation purity, tests were done on turmeric powder. Then, extraction was done using solvents prepared using mixed solvency such as camphor in ethanol (25% w/v and 50% w/v) and thymol in ethanol (25% w/v and 50% w/v). In addition, identification tests were done on the obtained extract. The comparative study was done on extraction yields, to establish a comparison between the yield obtained using conventional solvent and solvents prepared using the mixed solvency concept. In addition to that, a topical formulation was also prepared for the obtained extract. For formulation development solubility, studies of turmeric extract were done in various oils, ethanol, and blends (constituted in ethyl oleate with the combination of additives such as methyl paraben, propyl paraben, glyceryl monostearate, benzyl benzoate, and benzoic acid). The formulation so formed was a 0.9% curcumin oily solution and the evaluation tests such as viscosity, drug excipients interaction studies, and in vitro release studies were also done for the same. Results: In the extraction, it was discovered that adding camphor and thymol to ethanol improves the yield of turmeric extract, as compared to ethanol. Solubility studies were done for the preparation of topical solution and topical emulgel. The maximum solubility of turmeric extract was perceived in an oily blend which was formed by the purport of the mixed solvency concept). As a result, the oil base chosen for the formulation was an oily blend rather than a single oil or ethanol. In which the formulation produced positive outcomes. Evaluation studies such as freeze thaw, in vitro drug release, and antibacterial activity were performed for the formulation and it showed virtuous results.